Hybanthus parviflorus (Violaceae): Insecticidal activity of a South American plant - Broussalis, Adriana Maria (2010)
Hybanthus parviflorus is a perennial shrub, widely distributed in the tropical and subtropical regions of America, and is known as 'violetilla' in Argentina. Previous phytochemical studies of this species led us to the isolation and determination of the primary structure of a novel macrocyclic polypeptide, the cyclotide hypa A. Here the insecticidal activities of extracts of H. parviflorus were determined against Ceratitis capitata Wied., the Mediterranean fruit fly or 'Medfly'. Mortality in the different life stages of Medfly, total mortality and modifications of the insect's physiology caused by 50% EtOH and CH2Cl2 extracts of H. parviflorus were evaluated. In addition, we determined the occurrence of ursolic acid, β-sitosterol and the polyphenols quercetin, quercetin-3-methyl ether, apigenin, luteolin, kaempferol, rutin, caffeic acid and chlorogenic acid. The promising insecticidal activity of 50% EtOH extracts of H. parviflorus and its purified fractions was related to the presence of cyclotides. The insecticidal activity of CH2Cl2 extracts could be related to the presence of polyphenols, ursolic acid and β-sitosterol.